Cytotoxic and Anti-Inflammatory Activities of Garcinia xanthochymus Extracts on Cell Lines - Hamidon, Hanisuhana; Taher, Muhammad; Jaffri, Juliana M; Tg Zakaria, Tg M; Sulaiman, Wan MAW; Susanti, Deny; Ichwan, Solachuddin JA; Zakaria, Zainul A (Makara Journal of Health Research, 2016)
Background: Garcinia xanthochymus extract has been reported to have several pharmacological properties. This study was conducted to evaluate cytotoxic and anti-inflammatory activities of G. xanthochymus extracts on cell lines. Methods: The roots and stem barks of plant were extracted using maceration method with n-hexane, dichloromethane and methanol, successively. Cytotoxic activity of the extracts was tested against MCF-7 breast adenocarcinoma using MTT assay. Anti-inflammatory study was evaluated using RAW 264.7 mouse macrophage cells. The nitric oxide production in LPS-stimulated cells was measured using Griess reagent. Results: The results of cytotoxic and anti-inflammatory study showed that dichloromethane and n-hexane extracts of root and stem bark exhibited cytotoxic activity in dose-dependent manner. Meanwhile, for anti-inflammatory study, all root extracts together with stem bark dichloromethane and n-hexane extracts reduce NO production in LPS-stimulated cells in dose dependent manner. Conclusions: This finding indicated that G. xanthochymus extracts might become interesting candidate for treatment of cancer and inflammation.